Study on the Effect of Nano Zirconia Additive on the Tribological Properties of Lubricating Grease - JIA Qi-su, XU Shi-peng, ZHAO Jie-ge (Cailiao Baohu, 2021)
Aiming at studying the effect of nano zirconia as additive on the tribological properties of lubricating grease, the lubricating grease with different proportion of nano zirconia was prepared. The influence of nano zirconia on the tribological properties of lubricating grease was studied by four ball friction tester and high-temperature reciprocating friction and wear tester. Furthermore, the Nano-ZrO2 was characterized by laser particle analyzer, powder X-ray diffractometer and Fourier transform infrared spectrometer. The 3D profiles of worn surfaces were characterized by metallographic microscope and three-dimensional topography instrument. Results showed that the performance of the grease can be optimized by adding nano zirconia, the optimal adding ratio was 0.3%, and the optimal working temperature was 50 ℃. In the comparison of the original grease, the average friction coefficient decreased by 16.87%, the diameter of grinding spot of steel ball declined by 11.48%, the mass loss of steel ball was reduced by 74.72%, and the average height of grinding spot of steel ball declined by 33.16%.